APROXIMACIÓN A LOS DIALOGI DEL PAPA GREGORIO MAGNO, A PROPÓSITO DE LOS SUSTANTIVOS VIR, HOMO Y VIRTUS - Beltrán Corbalán, Domingo (Antigüedad y Cristianismo, 1995)
In this article our objective is to obtain a better understandding of Gregorio Magno's Dialogi by means of the language he uses. In order to do so we selected three nouns which we believe to be the most important when one narrates the lives and miracles of the saints: vir, homo and virtus. Our aim is to discover what was Gregorio Magno's concept of these terms. (...)